2019
DOI: 10.1002/maco.201911135
|View full text |Cite
|
Sign up to set email alerts
|

Anode characteristics of Al/Ti galvanic couple in a salt spray environment

Abstract: The galvanic corrosion behavior of a 2A12 aluminum alloy and a Ti-15-3 titanium alloy in a salt spray environment was investigated. The results indicated that the galvanic effect accelerated the dissolution rate of the anodes significantly; however, the corrosion of the anode was not uniform. The region adjacent to the coupled joint experienced the most significant corrosion, with galvanic corrosive action emerging as dominant. The corrosion of the region distant from the joint was slight and was dominated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The previous investigation revealed that Ti had outstanding anti-corrosion property in artificial seawater environments because of its thin and stable passive film [19]. After the Al alloy was coupled with Ti, Al had low potential and served as the anode and Ti acted as the cathode due to its high potential [20]. Region ii was considered to be the corrosion products of the Al-Mg phase near the Ti particle.…”
Section: Fib-tem Investigation Of the Impmentioning
confidence: 99%
“…The previous investigation revealed that Ti had outstanding anti-corrosion property in artificial seawater environments because of its thin and stable passive film [19]. After the Al alloy was coupled with Ti, Al had low potential and served as the anode and Ti acted as the cathode due to its high potential [20]. Region ii was considered to be the corrosion products of the Al-Mg phase near the Ti particle.…”
Section: Fib-tem Investigation Of the Impmentioning
confidence: 99%